Análise luminotécnica de salas de aula da Escola Municipal Ensino Fundamental Governador Fernando José de Leão Guilhon no município de Tucuruí-PA - BARBOSA, Felipe José Ribeiro (2018)
This paper has as aim to analyze two lighting systems and their efficiency in classrooms of Elementary School Governor Fernando Jose Leao Guilhon, located in Tucurui, municipality in the state of Pará. The research was done through an analysis of a downtown plant of the school entered in a computer program called AutoCAD 2011. After making the projection of the plant classrooms coming from the autoCAD, it was possible to perform the analysis of lighting projects. The program used to scale the new lighting system was the DIALux EVO 6. For this study we used the two simulations, corresponding to EFix and Power Balance fixtures. The results were analyzed with the requirements of ISO-5413 5413 and NBR ISO/CIE 8995-1/2013. The research was carried out of the influence of the lighting for the quality of teaching and learning and realized adequacy proposal for the most appropriated to the enviroment fixtures system. In the case of school Fernando Guilhon, which was recently renewed, each classroom actually has 12 (twelve) fluorescent lamps, some rooms have burned out lamps, which often are not replaced immediately, or are replaced by fluorescent compact lamps. For this reason the use of natural lighting should be studied and used in order to balance its benefits and reduce its negative effects. The level of illuminance obtained through simulations with lightning models TCS260 2xTL5 - 28W HFP and RC460B W60L60 1xLED28S / 840 attends to NBR 5413 5413 and NBR ISO/CIE 8995-1/2013, where the illuminance for classrooms should be on average between 200, 300 or 550 lux as shown in the simulations by DIALux EVO. In order to establish a more appropriated system of lighting for classrooms of the Elementary School Governor Fernando Jose Guilhon, we can consider that the luminaire model RC460B W60L60 1xLED28S / 840 are more suitable as they provide a more constant illumination and level, allowing the use of natural light. The lighting design for classrooms should be very careful so that it can provide a very proper and pleasing visual environment to perform school tasks, to increase performance in the teaching-learning relationship. We noticed that for the lighting of classrooms is done correctly and optimally, it is necessary to check several factors, procedures and analyzes. But the importance of proper lighting in classroom goes beyond the quality of the service aspect also includes the electricity savings, the government through the Procel, encourages schools to work the awareness of students at all educational levels, as respect and energy efficiency.